The Influence of Planning, Reporting, Standard Operating Procedure on University Education Costs Management Accountability - Ratih Kusumastuti; Matin Matin; Siti Rochanah (STAI Hubbulwathan Duri, 2021)
The management of educational institutions requires accountability for managing education costs related to the management of school financing. Accountability is a concept of openness in education management. This study aimed to determine the effect of planning, reporting, and standard operating procedures on the accountability of the management of education costs. This research used quantitative research. Participants were employees of the University of Indonesia. Data in the form of a questionnaire was taken using a survey method. Data analysis used regression analysis. The results of the study concluded that 1) there is a direct positive effect of planning on the accountability of the management of education costs (t-count 2.406 t-table 2.08), 2) there is a direct positive effect of reporting on the accountability of the management of education costs (t-count 2.981 t-table 2.08), and 3). there is a direct positive effect of standard operating procedures on the accountability of the management of education costs (t-count 2.547 t-table 2.08). This also impacts the efficiency level of accountability in education cost management at the University of Indonesia.